Triple hydrogen atom abstraction from Mn–NH3 complexes results in cyclophosphazenium cations. Issue 93 (6th November 2019) - Cook, Brian J.; Johnson, Samantha I.; Chambers, Geoffrey M.; Kaminsky, Werner; Bullock, R. Morris
Abstract : All three H atoms of the NH3 ligand of [Mn(depe)2 (CO)(NH3 )] + are abstracted by an organic radical, giving a rare cyclophosphazenium cation; computations suggest that insertion of NH x into a Mn–P bond provides a strong thermodynamic driving force. Abstract : All hydrogen atoms of the NH3 in [Mn(depe)2 (CO)(NH3 )] + are abstracted by 2, 4, 6-tri- tert -butylphenoxyl radical, resulting in the isolation of a rare cyclophosphazenium cation, [(Et2 P(CH2 )2 PEt2 )N] +, in 76% yield. An analogous reaction is observed for [Mn(dppe)2 (CO)(NH3 )] + . Computations suggest insertion of NH x into a Mn–P bond provides the thermodynamic driving force. Contextualization of this reaction provides insights on catalyst design and breaking strong N–H bonds.